2009
DOI: 10.1542/peds.2008-1590
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed Moisture Damage at Home, Respiratory Symptoms and Atopy in Early Life: A Birth-Cohort Study

Abstract: This birth-cohort study supports previous observations that moisture mold problems in the kitchen and in the main living area increase the risk for wheezing in early childhood. The results underline the importance of assessing separately the health effects of moisture and mold problems in different areas of the home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
106
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 29 publications
8
106
1
2
Order By: Relevance
“…Mold and dampness in the children's homes were evaluated by parents in the questionnaire, and showed strong positive associations with most of the children's allergic symptoms in this study. This positive association agrees with reviews in the scientific literature [34,35], and with many cross-sectional [36] and birth-cohort studies [9,37] studies of dampness in home environments and children's asthmatic and allergic diseases in western countries. Studies from Taiwan, China, also support the positive association of indoor dampness with childhood asthma [38].…”
Section: Resultssupporting
confidence: 88%
“…Mold and dampness in the children's homes were evaluated by parents in the questionnaire, and showed strong positive associations with most of the children's allergic symptoms in this study. This positive association agrees with reviews in the scientific literature [34,35], and with many cross-sectional [36] and birth-cohort studies [9,37] studies of dampness in home environments and children's asthmatic and allergic diseases in western countries. Studies from Taiwan, China, also support the positive association of indoor dampness with childhood asthma [38].…”
Section: Resultssupporting
confidence: 88%
“…Visible mould exposure Wheeze Of the nine publications evaluating the longitudinal effect of early exposure to visible mould at home and wheezing in the first 3 yrs of life, seven studies observed a significant positive association [8,12,36,41,42,48,49]. In one US birth cohort study (the Cincinnati Childhood Allergy and Air Pollution Study) from IOSSIFOVA et al [8], the reported increase in risk was persistent from 1-3 yrs of age.…”
Section: Resultsmentioning
confidence: 99%
“…DIJKSTRA [29] DALES [16] DALES [32] PONSONBY [18] ZHENG [27] CHEN [25] FREEMAN [20] FREEMAN substudy [20] SPENGLER [19] PEKKANEN [33] DONG [17] DONG [22] ANTOVA [15] WARMAN [24] Summary (OR FAGBULE [34] VERHOEFF [31] LI [26] LI [35] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] BRUNEKREEF [21] STRACHAN [37] STRACHAN [38] DIJKSTRA [29] DALES [16] SPENGLER [19] EMENIUS [36] ALPER [39] DONG [17] DONG [22] ANTOVA [15] ROSENBAUM [43] IOSSIFOVA [8] KARVONEN [42] Summary (OR LI [26] MAIER [28] BRUNEKREEF [23] BRUNEKREEF [23] CHEN [25] BIAGINI [45] IBARGOYEN-ROTETA [44] KOSKINEN substudy [47] KOSKINEN [47] LI [26] LI [35] BRUNEKREEF [21] DONG …”
Section: Discussionmentioning
confidence: 99%
“…The Lifeways study was one of the first to show that general practitioner-reported wheeze or asthma (52) Czech Republic 7577 1994 x Devereux et al (53) UK 1400 1997 x x Drouillet et al (54) France 1900 2003 x x x x Dubois et al (55) Canada 1450 1998 x x Eggesbo et al (56) Norway 2500 2003 x x x Emanuel et al (57) UK 3076 1958 x Gorden-Larsen et al (58) USA 14 706 1995 x Gracie et al (59) Canada 3388 2008 x x Grandjean et al (60) Faroe Islands 1022 1986 x x x x Guldner et al (61) France 4000 2002 x x Guxens et al (62) Spain 3768 1997 x x x x x Grazuleviciene et al (63) Lithuania 4405 2007 x Hawkes et al (64) Ireland 2185 2008 x Hawkins et al (65) UK 13 113 2000 x Hill et al (66) Wales 420 2009 x x Hryhorczuk et al (67) Ukraine 4510 1992 x x x Hui et al (68) Hong Kong 8327 1997 x x Hunt et al (69) Canada 521 1981 x x Inskip et al (70) UK 3159 1998 x x Jaddoe et al (71) Netherlands 10 000 2002 x Jedrychowski et al (72) Poland 432 2000 x x Kaplowitz et al (73) UK 224 1986 x x Karvonen et al (74) Finland 442 2002 x x x x Katier et al (75) Netherlands 2500 (95) Germany 2000 2011 x x x x Richiardi et al (96) Italy 7500 2005 x x x x Schaefer-Graf et al (97) Germany 324 1995 † x x Sekine et al (98) Japan 8941 1992 x x Skalkidou et al (99) Sweden 580 2009 x x Tsuchiya et al (100) Japan 1260 2007 x x van Eijsden et al (101) The Netherlands 6161 2003 x x x x Vandentorren et al (102) France 20 000 2011 x x x Vecchi Brumatti et al (103) Italy 900 when the child averaged 3 years was inversely associated with maternal fruit and vegetable and fish consumption during pregnancy (1...…”
Section: Dietary Patterns and Risk Of Childhood Wheezing Or Asthmamentioning
confidence: 99%